Infant feeding practices in an urban tertiary care hospital: A descriptive longitudinal study - Hegde, Jayashree; Manjula, L; Venkatesha, K R (Indian Journal of Child Health, 2017)
Background: Infant and young child feeding are the corner stone for child development. More than a third of the world’s undernourished children reside in India. Inadequate infant and young child feeding practices with inadequate care and management of common illnesses contributes to malnutrition. Objective: To study the prevailing infant feeding practices and determine influence of factors on infant feeding in a tertiary care hospital. Materials and Methods: A descriptive longitudinal follow-up study was conducted in a tertiary care hospital between November 2010 and April 2012. Maternal and baby’s profiles were obtained using oral questionnaire after birth by personal one-to-one interview. These cases were followed up for their infant feeding practices till 1 year of age in outpatient department and also by telephonic conversation. Continous variables were analysed by mean and SD. For categorical variable frequency and percentage were determined. Results: 61.25% mothers had initiated breastfeeding within 1 h. Prelacteal feed was given to 28.6% babies. 61.5% had initiated complementary feed at 6 months. Bottle feeding was preferred mode of feeding. There was a statistically significant association between initiation of breastfeeding and parity (p=0.022) and type ofdelivery (p